A Study on Parthenogenesis of Petersen Graph - Siti Amiroch; Danang Kiratama ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2017)
Genetics is the science of trait from the parent to the descendant. In biology, genetics pass a series of genes unification process that takes place in the chromosome. The results of genes unification will form the nature and character of the generation. This particular genetic process also applies in graph theory. Genetics on graph theory is divided into two: breeding and parthenogenesis. This present study elaborated a single type of genetic processes that was parthenogenesis which is applied on a Petersen graph. Through the similar process to genetics in biology, Petersen graph will be reconstructed and combined with other graphs (gene) in purposes to create a descendant or a new graph with new nature and characteristic. Based on the result of parthenogenesis on this Petersen graph, there was derived a graph which has 18 edges and 12 vertices, isomorphism toward another Petersen graph, Hamiltonian, and has 3 girth and symmetric.